Hubungan Status Pekerjaan Ibu dengan Pemberian ASI Eksklusif di Wilayah Kerja UPT Puskesmas Menteng Tahun 2022: The Correlations the Mother’s Employment Status with the Giving Gexclusive Breastfeeding in the Working Area Of UPT Puskesmas Menteng in 2022 - Fransiska Olya; Fitriani Ningsih; Riska Ovany (Jurnal Surya Medika (JSM), 2023)
Exclusive breastfeeding was the feeding of breast milk as soon as the baby was born until the baby was 6 months old without the addition of other foods, such as formula milk, porridge and biscuits. The administration of minerals, vitamins and medicines can be given in liquid form as recommended by the doctor. The coverage of exclusive breastfeeding in Puskesmas Menteng area in 2021 was 27.82% who were given exclusive breastfeeding. The purpose of the study was to find out the Correlationf of the mother's employment status with exclusive breastfeeding. The design of this research was an analytical descriptive study with a cross-sectional approach. The method used was proposive sempling. samples were taken as many as 62 mothers who had babies of 0-12 months who visited at Puskesmas Menteng. Data collection uses questionnaires containing the characteristics of respondents. After tabulating the existing data were analyzed using Univariate and Bivariate analysis. Based on the research result, it may be concluded the statistical test analysis study with the chi square test obtained a value of P = 0.016< (a 0.05) which means that there was a significant relationship between the mother's employment status and exclusive breastfeeding in the work area of the UPT Puskesmas Menteng in 2022. The role of health workers in preparing mothers to investigate can touch all circles by utilizing existing technological advances such as counseling using social media such as WhatsApp so that it was easily accessed directly by the communities.